Hedyotis tonggulingensis (Rubiaceae): A new species from Hainan, China - Jiang, Guo-Bin; Wang, Rui-Jiang (Phytotaxa, 2019)
Hedyotis tonggulingensis is described as a new species from China. It is similar to the sympatric species H. hainanensis, but obviously differs in having tetragonal stems with narrow wings, terminal and axillary inflorescences and the short corolla tubes. The phylogenetic analysis revealed that H. tonggulingensis was closely related to the sympatric species of H. pardifolia and H. yazhouensis but not to H. hainanensis. It was evaluated as Least Concern because of its abundant individuals, little economic use and well protected habitat.